ASSOCIATION OF SENSORY IMPAIRMENT WITH HEALTHCARE UTILIZATION AND COSTS IN ADULTS WITH AND WITHOUT DEMENTIA. (11th November 2018) - Deardorff, W; Liu, P; Sloane, R; Van Houtven, C; Hastings, S; Cohen, H; Whitson, H
Abstract: Combinations of sensory and cognitive impairments are common and associated with significant disability. We examined the association between self-reported hearing impairment (HI), vision impairment (VI), and dual sensory impairment (DSI), stratified by dementia status, on hospital admissions and healthcare costs. We used a nationally representative sample of 24, 009 community-dwelling adults aged 65+ years from the Medicare Current Beneficiary Survey between 1999–2006. Dementia status was determined by self-report or diagnosis codes in claims data. Primary outcomes included risk of hospital admission (derived from Medicare claims), Medicare Fee-for-Service costs (verified by Medicare claims), and total healthcare costs (combining Medicare claims and other self-reported payments). Self-reported DSI was present in 30.2% (n=263/871) of participants with dementia and 17.8% (n=4, 112/23, 138) without dementia. In multivariable logistic regression models, HI, VI, or DSI were associated with increased odds of hospitalization regardless of dementia status. In a generalized linear model with Gamma distribution and log-link adjusted for demographics, annual total healthcare costs were greater for those with dementia and DSI compared to without dementia and with DSI ($28, 875 vs. $3, 340, respectively). Presence of any sensory impairment was generally associated with higher costs. However, in fully adjusted models including demographics, Medicaid status, and chronic conditions, DSI compared with no sensory impairment was not associated with much higher costs in those with dementia ($11, 303 vs. $10, 466, p=0.395) or without dementia ($1, 151 vs. $1, 056, p<0.001). Our results highlight the dramatic healthcare costs associated with dementia and identify a vulnerable population with sensory and cognitive impairments who are high healthcare utilizers.